Timing of adjuvant chemoradiation for pancreatic cancer with positive surgical margins - ALKIŞ, HİLAL; ADLI, MUSTAFA (My University, 2023)
Aims: Impact of adjuvant chemoradiation timing on the outcome of pancreatic cancer patients with positive surgical margins is unknown. The aim of this study was to evaluate the effect of adjuvant chemoradiation timing for margin positive pancreatic cancer patients. Methods: A total of 36 pancreatic adenocarcinoma patients with positive surgical margins and received adjuvant chemoradiation were included in the study. The median radiation dose was 50.4 Gy in 28 fractions. The primary study variable was the timing of chemoradiation, grouped as immediate (after ≤ 1 cycle of chemotherapy) and delayed (after two or more cycles of chemotherapy) chemoradiation. Gemcitabine (n=16) and capecitabine (n=20) were chemotherapy regimens administered with radiation. Results: Median follow-up time was 23.7 months. Thirteen patients (36%) received immediate and 23 (64%) received delayed chemoradiation. For immediate and delayed treatment groups, median overall survival was 13.5 and 42.5 months, and disease-free survival was 6.4 and 18.8 months, respectively. Disease-free survival and overall survival were better with delayed chemoradiation (p=0.02). However, the two groups did not significantly differ in locoregional control (p=0.96). Conclusion: Delaying chemoradiation until completion of systemic therapy improves disease-free survival and overall survival without any difference in locoregional failure compared to early chemoradiation in pancreatic cancer patients with positive surgical margins.
Keywords: Pancreatic cancer; positive margin; chemoradiation timing; prognosis